Establishment and validation of nomograms to predict survival probability of advanced malignant pleural mesothelioma based on the SEER database and a Chinese medical institution - Zhang, Xuemei; Chang, Lele; Zhu, Yingying; Mao, Yuxin; Zhang, Tao; Zhang, Qian; Wang, Chunbo (Frontiers in Endocrinology, 2023)
Objective The purpose of this study was to build nomograms for predicting the survival of individual advanced pleural mesothelioma (MPM) patients using the Surveillance, Epidemiology, and End Results (SEER) database. Methods The 1251 patients enrolled from the SEER database were randomized (in a 7:3 ratio) to a training cohort and an internal validation cohort. Eighty patients were enrolled from the Harbin Medical University Cancer Hospital as the external validation cohort. Nomograms were constructed from variables screened by univariate or multivariate Cox regression analyses and evaluated by consistency indices (C-index), calibration plots, and receiver operating characteristic (ROC) curves. Patients from the SEER database who received chemotherapy alone and chemoradiotherapy were statistically paired using propensity score matching of the two groups and performed subgroup analysis in the screened variables. Results The nomograms are well-structured and well-validated prognostic maps constructed from four variables: gender, histology, AJCC stage, and treatment. All individuals were allocated into high-risk versus low-risk groups based on the median risk score of the training cohort, with the high-risk group having worse OS and CSS in all three cohorts (P<0.05). The outcomes of the subgroup analysis indicated that the advanced MPM patients receiving chemotherapy with or without local radiotherapy do not affect OS or CSS. Conclusion The accurate nomograms to predict the survival of patients with advanced MPM were built and validated based on an analysis of the SEER database with an external validation cohort. The study suggests that the additional local radiotherapy to chemotherapy does not increase the survival benefit of patients.